2022
DOI: 10.4330/wjc.v14.i12.626
|View full text |Cite
|
Sign up to set email alerts
|

Impact of the virtual anti-hypertensive educational campaign towards knowledge, attitude, and practice of hypertension management during the COVID-19 pandemic

Abstract: BACKGROUND One of the efforts to reduce hypertension rates in the community is through an educational campaign that refers to the NIH's National Heart, Lung, and Blood Institute curricula or abbreviated as NHLBI. However, during the coronavirus disease 2019 (COVID-19) pandemic, one of the hardest hit areas is health promotion, and there is a significant obstacle regarding the most effective way to transfer knowledge, attitude and practice towards society without transmitting the virus. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
6
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(6 citation statements)
references
References 28 publications
0
6
0
Order By: Relevance
“…To address the global burden of hypertension, the Lancet commission encourages governments, pharmaceutical companies, healthcare professionals, and professional societies to develop simple mobile apps and online education programs to provide equal basic health access to people in low-income and middle-income countries[ 9 ]. In sync with this concept, the study conducted by Andrianto et al [ 1 ] reveals the importance of anti-hypertensive education in lower-middle-income countries. They found that virtual anti-hypertensive educational campaign implementation led to a significant improvement in the knowledge and attitude of patients with hypertension; however, it did not reflect a change in patient practice in taking measures against hypertension[ 1 ].…”
Section: To the Editormentioning
confidence: 98%
See 4 more Smart Citations
“…To address the global burden of hypertension, the Lancet commission encourages governments, pharmaceutical companies, healthcare professionals, and professional societies to develop simple mobile apps and online education programs to provide equal basic health access to people in low-income and middle-income countries[ 9 ]. In sync with this concept, the study conducted by Andrianto et al [ 1 ] reveals the importance of anti-hypertensive education in lower-middle-income countries. They found that virtual anti-hypertensive educational campaign implementation led to a significant improvement in the knowledge and attitude of patients with hypertension; however, it did not reflect a change in patient practice in taking measures against hypertension[ 1 ].…”
Section: To the Editormentioning
confidence: 98%
“…In sync with this concept, the study conducted by Andrianto et al [ 1 ] reveals the importance of anti-hypertensive education in lower-middle-income countries. They found that virtual anti-hypertensive educational campaign implementation led to a significant improvement in the knowledge and attitude of patients with hypertension; however, it did not reflect a change in patient practice in taking measures against hypertension[ 1 ].…”
Section: To the Editormentioning
confidence: 98%
See 3 more Smart Citations